Post-marketing safety evaluation of lurbinectedin: a pharmacovigilance analysis based on the FAERS database - Li, Zhao; Guo, Changying; Liu, Xingfei; Qiu, Zhengzhou; Zhang, Ruilin (Frontiers in Pharmacology, 2024)
Background: On June 15, 2020, the United States Food and Drug Administration (FDA) approved lurbinectedin for treating adult patients with metastatic small-cell lung cancer whose disease has progressed despite prior platinum-based chemotherapy. Following its market approval, safety data on lurbinectedin in large populations is currently lacking. Therefore, this study aims to evaluate adverse events (AEs) associated with lurbinectedin using the FDA's Adverse Event Reporting System (FAERS)database. Methods: Data concerning lurbinectedin from the FAERS database were extracted for the period from June 2020 to September 2023. Four disproportionality analysis algorithms were utilized to assess potential AEs linked to lurbinectedin: reporting odds ratio (ROR), proportional reporting ratio, disproportionate multi-item gamma Poisson shrinker, and Bayesian confidence propagation neural network. These algorithms were applied to quantify signals of lurbinectedin-related AEs. Result: A total of 5,801,535 AE reports were retrieved from the FAERS database, with 511 related to lurbinectedin. These lurbinectedin-induced AEs were observed in 23 system organ classes (SOCs). After simultaneously applying the four algorithms, 47 lurbinectedin-induced AE signals were detected in 23 SOCs. At the SOC level, blood and lymphatic system disorders (ROR, 6.70; 95% confidence interval [CI]: 5.47–8.22) were the only SOC that met all four algorithms. Lurbinectedin's most frequent adverse event was death (ROR: 6.11, 95% CI: 4.86–7.68), while extravasation exhibited the strongest signal intensity in the ROR algorithm (ROR: 326.37, 95% CI: 191.66–555.75). Notably, we identified a novel signals: tumor lysis syndrome (ROR: 63.22, 95% CI: 33.87–117.99). The mean time of onset of AEs was 66 days, the median time of onset was 25 days (interquartile range: 8–64 days), and most AEs occurred within the first month of lurbinectedin treatment. Conclusion: Our study provided a comprehensive evaluation of lurbinectedin's safety profile in the post-marketing setting. In addition to the adverse events consistent with the existing clinical trials and labeling information, we have also identified an unreported signal related to tumor lysis syndrome. This finding will better guide the clinical practice of lurbinectedin and provide valuable evidence for future research.